2019
DOI: 10.1063/1.5053887
|View full text |Cite
|
Sign up to set email alerts
|

A Lagrangian fibration of the isotropic 3-dimensional harmonic oscillator with monodromy

Abstract: The isotropic harmonic oscillator in dimension 3 separates in several different coordinate systems. Separating in a particular coordinate system defines a system of three Poisson commuting integrals and, correspondingly, three commuting operators, one of which is the Hamiltonian. We show that the Lagrangian fibration defined by the Hamiltonian, the z component of the angular momentum, and a quartic integral obtained from separation in prolate spheroidal coordinates has a non-degenerate focus-focus point, and h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…In two recent papers, 17,18 we have used separation in spheroidal coordinates for the Kepler problem in space and the harmonic oscillator in space, respectively, and shown that both problems—when considered in prolate spheroidal variables—have Hamiltonian and quantum monodromy. The present paper grew out of the realization that an even simpler problem, namely, the free particle, can be studied in a similar way, and leads to similar results, namely, monodromy in the joint spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…In two recent papers, 17,18 we have used separation in spheroidal coordinates for the Kepler problem in space and the harmonic oscillator in space, respectively, and shown that both problems—when considered in prolate spheroidal variables—have Hamiltonian and quantum monodromy. The present paper grew out of the realization that an even simpler problem, namely, the free particle, can be studied in a similar way, and leads to similar results, namely, monodromy in the joint spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…In two recent papers [DW18] and [CDEW19] we have used separation in spheroidal coordinates for the Kepler problem in space and the harmonic oscillator in space, respectively, and shown that both problems -when considered in prolate spheroidal variables -have Hamiltonian and quantum monodromy. The present paper grew out of the realisation that an even simpler problem, namely the free particle, can be studied in a similar vain, and leads to similar results, namely monodromy in the joint spectrum.…”
Section: Introductionmentioning
confidence: 99%